The center of everything - Urban, Linda (Harcourt Children's Books / Houghton, Mifflin, Harcourt, 2013)
For Ruby Pepperdine, the center of everything is on the rooftop of Pepperdine Motors, stargazing from the circle of her grandmother Gigi's hug. That's how everything is supposed to be...until it goes spinning out of control. Now Ruby's best friend, Lucy, is mad at her. Her new friendship with Nero is pretty bumpy too. Worst of all, Ruby regrets what happened with Gigi. How Ruby didn't listen. And now it's too late to make things right. But Ruby has one last hope. It all depends on what happens on Bunning Day, when the entire town will hear her read her winning essay. And it all depends on her twelfth birthday wish... unless she messes that up too
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Children's stories; Jugendbuch